Efficient mechanochemical synthesis of new fluorinated Schiff bases: a solvent-free, alternative to conventional method with mercury adsorption properties - Mirza T. Baig (14152407) (2025)
The development of sustainable synthetic techniques is of critical importance in modern chemistry. This paper describes a mechanochemical approach to the synthesis of novel fluorinated Schiff bases via ball milling, which provides a fast, high-yield, and green alternative to conventional reflux methods. The synthesized fluorinated Schiff bases are evaluated for their adsorption capacity and efficiency in mercury removal and compared to assess their performance, demonstrating that ball milling produced compounds with comparable physical attributes to those produced via traditional solvent-based procedures. However, ball milling considerably shortened reaction time, with some reactions taking less than 5 min, and enhanced yields, reaching up to 92%, which is significantly higher than that achieved by conventional methods. The molecular structure of the synthesised Schiff bases is validated using analytical and spectroscopic techniques, including 1H, 13C NMR and mass spectroscopy, with chemical shifts confirming the expected structures. Furthermore, the thermal stability of the synthesized Schiff bases is validated up to around 250 °C, demonstrating their robustness and suitability for various applications. Given their well-established chelating properties, the selected Schiff bases (M6-M9) are studied for mercury adsorption. Structural variations, such as hydroxyl and carbonyl functionalities, are anticipated to enhance mercury binding, making these compounds potential candidates for environmental remediation. Notably, this research presents the first investigation of these specific fluorinated Schiff bases for mercury chelation, demonstrating notable adsorption for mercury and highlighting their potential in heavy metal remediation. Other Information Published in: BMC Chemistry License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s13065-025-01552-9